Enhancing Chatter Resistance in Deep Hole Boring Through Modified Tool Design: A Study on Impact of Length-To-Diameter (L/D) Ratio - Gopalakrishna H.D; Shraddha A; Gourav Vivek Kulkarni (International Journal of Machine Systems and Manufacturing Technology, 2024)
Deep hole boring is a specialized machining process crucial for creating precise bores with high length-to-diameter (L/D) ratios, particularly vital in aerospace, automotive, and oil and gas industries. The L/D ratio is pivotal for stability and performance. Chatter, a detrimental vibration phenomenon, is a significant concern in deep hole boring, influenced by the L/D ratio. Higher L/D ratios increase chatter, leading to poor surface finish and reduced tool life. Longer tool lengths in high L/D ratios reduce damping effects, increasing chatter and impacting machined surface quality. Strategies for mitigating chatter include tailoring tool geometries, implementing damping methods, and adjusting cutting parameters based on specific L/D ratios for optimization. The study employs a three-phase methodology to enhance the dynamic performance of a standard AISI 4340 steel boring tool, S25T SCLCR 09 T3, with a modified version featuring a damper. Modal and harmonic analyses, both numerical and experimental, are conducted to evaluate the natural frequencies, mode shapes, damping ratios, and response to periodic loads. Boring operations are performed under constant conditions, and surface roughness measurements are taken for both the solid and modified tools. The results reveal that the modified tool consistently exhibits lower natural frequencies and higher damping ratios, indicating improved stability during machining. Surface roughness measurements demonstrate a significant percentage improvement for the modified tool, highlighting its effectiveness in enhancing machining precision and chatter resistance. The study contributes valuable insights into the impact of length-to-diameter (L/D) ratio on tool performance, offering practical implications for optimizing machining conditions.
Keywords: Chatter; Monitoring; composite; instability; suppression